High-Frequency Modeling of Coplanar Waveguides Including Surface Roughness - Gold, Gerald; Lomakin, Konstantin; Helmreich, Klaus; Arz, Uwe (Advances in Radio Science, 2019)
An existing analytical transmission line model to describe propagation properties of coplanar waveguides including dispersion and radiation effects was extended to take into account surface roughness of conductor traces. The influence of parasitics is successively included in the simulation and compared to measurements. The device under test (DUT) was fabricated on an Al2O3 wafer. A metal and ceramic chuck was utilized during measurements up to 120 GHz. The extended model is then capable of precisely predicting propagation properties in a wide frequency range and can now be used for calibration purposes like the development of uncertainty budget